From Centrosymmetry to Noncentrosymmetry: Tailoring the Structural Arrangements of Carbonates with Strong Nonlinear Optical Response through Partial Anion Substitution. Issue 16 (22nd May 2021) - Meng, Xianghe; Gong, Pifu; Tang, Chunlan; Yin, Wenlong; Lin, Zheshuai; Xia, Mingjun
Abstract: Second‐harmonic nonlinear‐optical (NLO) crystals with intrinsically noncentrosymmetric (NCS) structures are the core crystalline materials in the modern optics and laser technology. Here, taking as‐grown centrosymmetric NaY(CO3 )2 and NCS YOHCO3 crystals as an example, a partial anion substitution strategy in the carbonate system is provided to develop NLO materials with remarkable NLO property for the first time, while the outstanding linear optical properties such as wide bandgap and large birefringence are maintained. Notably, benefiting from the planar π‐conjugated (CO3 ) 2− anions and closed shell electronic structure of Y 3+ cations, the YOHCO3 crystal simultaneously manifests a deep UV cutoff (<200 nm), sturdy second‐harmonic‐generation signal (2 × KH2 PO4 ), and gigantic birefringence (0.07 at 1064 nm), enabling phase‐matching in short‐wavelength UV region. In addition, first‐principles calculations are conducted for the in‐depth analysis on the structure–optical property connection. Abstract : A partial anion substitution strategy realizes the transformation in carbonates from centrosymmetric NaY(CO3 )2 to noncentrosymmetric YOHCO3 for the first time. The as‐grown nonlinear optical crystal YOHCO3 has strong second‐harmonic generation effect, large birefringence, deep ultraviolet cutoff, and easiness in crystal growth.